Functional shape memory composite nanofibers with graphene oxide filler. (September 2015) - Tan, Lin; Gan, Lu; Hu, Jinlian; Zhu, Yong; Han, Jianping
Abstract: In the present study, we prepared a series of graphene oxide (GO) filled shape memory polyurethane (SMPU) nanofibers and systematically investigated the morphological, thermal and mechanical properties, surface wettability, and the shape memory effect (SME) followed by the proposed programming model. The results show that GO can be well dispersed within the SMPU matrix, and the introduction of GO significantly improves the mechanical strength, surface wettability, and thermal stability of the SMPU. Compared with pristine SMPU nanofibrous mats, the prepared SMPU/GO nanofibrous mats have better SME and lower thermal shrinkage. When the loading amount of GO increased to 4.0 wt%, the thermal shrinkage ratio ( R ts ) of composite nanofibrous mats could be as low as 4.7 ± 0.3%, while the average fixation ratio ( R f ) and recovery ratio ( R r ) could be as high as 92.1% and 96.5%, respectively. The study indicates that GO is a desirable reinforcing filler for preparing shape memory nanofibers with improved properties.